2003
DOI: 10.1161/01.cir.0000087593.07533.9b
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Clinical Benefits of Aspirin on First Myocardial Infarction by Nonsteroidal Antiinflammatory Drugs

Abstract: Background-There is clear evidence from numerous randomized trials and their meta-analyses that aspirin reduces risks of first myocardial infarction (MI). Recent data also suggest that other nonsteroidal anti-inflammatory drugs (NSAIDs) may interfere with this benefit of aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(103 citation statements)
references
References 30 publications
2
96
1
4
Order By: Relevance
“…20,21,32,33 Additionally, the concomitant administration of ibuprofen seems to antagonize the irreversible platelet inhibition induced by aspirin 34 and may also be associated with increased thrombotic complications. 35,36 Clopidogrel offers added antiplatelet efficacy to aspirin in patients with acute coronary syndromes 3 or after stent implantation. 6 It is possible, however, that the clinical benefit of clopidogrel is more complementary than additive.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,32,33 Additionally, the concomitant administration of ibuprofen seems to antagonize the irreversible platelet inhibition induced by aspirin 34 and may also be associated with increased thrombotic complications. 35,36 Clopidogrel offers added antiplatelet efficacy to aspirin in patients with acute coronary syndromes 3 or after stent implantation. 6 It is possible, however, that the clinical benefit of clopidogrel is more complementary than additive.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy volunteers, ibuprofen, but not diclofenac or rofecoxib, impaired aspirin's effect on thromboxane inhibition and platelet aggregation (19). Further evidence emerged from a subanalysis of the Physician's Health Study indicating that nonselective NSAIDs reduce the cardioprotective effect of aspirin in primary prevention of myocardial infarction (20). Moreover, a retrospective study from the United Kingdom concluded that concomitant aspirin and ibuprofen use was associated with an increased risk of cardiacrelated and all-cause mortality (21).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sustained exposure to diclofenac, rofecoxib or acetaminophen did not influence the effects of aspirin on platelet function. 94,95 To add to the controversy, another study on the effect of ibuprofen in aspirin-treated healthy adult volunteers showed no clinically meaningful loss of cardioprotection of aspirin when over-the-counter doses of ibuprofen were administered. 96 The gastroprotective benefit of COX-2 inhibitors is partially or, in some patients, totally lost if aspirin is used for cardiovascular prophylaxis.…”
Section: Drug Interactions Of Nsaidsmentioning
confidence: 99%